Pain and Suffering: In Conversation with Paul Ricœur - Jennifer Corns (Études Ricoeuriennes / Ricoeur Studies)
In this contribution, I focus on three key questions that arise when engaging with Ricœur’s lecture, “Suffering is Not Pain.” The first is the methodological issue concerning the philosopher’s role, particularly in taxonomizing. I will examine mental taxonomy, as well as taxonomy more broadly, before turning to pain and suffering more specifically. I then move to Ricœur’s characterization and contrast of suffering and pain throughout the lecture. Following this, I expand on Ricœur’s definition of suffering as a diminution of the power to act by incorporating my own account of suffering as a significant disruption to agency. I explore how this expanded view can contribute to a deeper investigation of Ricœur’s agentive hypothesis of suffering within each of his three identified “moments” of suffering, thus enhancing our understanding of the specific agentive challenge that suffering represents.